Quantitative analysis of cinema attendance success factors in France and the United Kingdom - Druet, Victor André Pierre Edouard (2024)
This study investigates the success drivers of the two neighboring French and British cinema exhibition industries over the past decade. The goal is first to explain their very different performance trajectories, including after the Covid-19 pandemic, and second to offer a framework that can allow cinema exhibitors to understand which factors have the most significant impact on their admissions. This quantitative research uses linear regressions to analyze the effects that economic, behavioral, and industry-related variables have had on the evolution of admissions per capita in the two countries: unemployment, inflation, and consumer confidence first; streaming platform and social media penetrations second; and average ticket price and number of cinemas and screens third. The results indicate that, overall, the two industries have reacted very differently to these variables, with unemployment and the total number of screens being considerably more significant in France than in the UK, where streaming platform penetration and ticket prices played a much more important role. Being a quantitative, comparative analysis tackling a business problem, this research is a valuable addition to the existing literature since such a study had not been done before, especially using post-Covid data. The results also allow to put into perspective the different innovation strategies that some cinema chains have implemented since 2014 and to identify which strategies could be most effective in the near future.